(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Stylistics applies modern linguistic theory to the description of and analysis into varieties of language and their stylistic features. Moreover, stylistics is the mostly used issue in the literary studies. For this reason, this study aims to explore the usage and application of stylistic devices in literature sphere. In addition, in this work we try to provide information on the notion of the basic stylistic theory, stylistics and its types. It aims at identifying the linguistic patterns of usage and meanings of literary works and demonstrating the formal aspects as well as their functional importance in the texts. As for the further examples, the present study is concerned with a stylistic analysis of Hemingway’s short stories